2021
DOI: 10.1017/jfm.2021.400
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear regimes of tsunami waves generated by a granular collapse

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 24 publications
1
27
1
1
Order By: Relevance
“…One obtains β ≈ 0.74 for the upper branch and β ≈ 0.45 for the lower one. It can be noted that the power law obtained for the upper branch is close to the values reported in the literature (see [24,26] and reference [23] which reports a power law η 0,max /H w = 1.23F r 0.8 max ), while the lower branch is more concave with lower values of wave amplitudes when F r max > 1. To the best of the authors' knowledge, this second branch has not been reported in the literature yet.…”
Section: Relevant Dimensionless Numbers Of Slide-to-wave Interactionsupporting
confidence: 86%
See 3 more Smart Citations
“…One obtains β ≈ 0.74 for the upper branch and β ≈ 0.45 for the lower one. It can be noted that the power law obtained for the upper branch is close to the values reported in the literature (see [24,26] and reference [23] which reports a power law η 0,max /H w = 1.23F r 0.8 max ), while the lower branch is more concave with lower values of wave amplitudes when F r max > 1. To the best of the authors' knowledge, this second branch has not been reported in the literature yet.…”
Section: Relevant Dimensionless Numbers Of Slide-to-wave Interactionsupporting
confidence: 86%
“…The dimensionless wave maximum amplitude is deduced from equations ( 24) and ( 25)-( 27), and shown in figure 12 along with numerical measurements. In the framework of the rectangular model, the actual dependency of the wave maximum amplitude with F r max is expected to lie in the blue shaded region (see figure 12) defined by equations (25) and (26) which can be considered as two end-members for the dependency of the celerity of perturbations with their own elevation. Recall that the model of rectangular collapse is expected to hold for slides which hardly deform, typically leading to solitary-like waves for F r max ≤ 0.58 (see figure 9).…”
Section: B Implications For Wave Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it would be interesting to compare these results to the axisymmetric case, where different scalings govern the final morphology of the deposit [3]. Besides, such a configuration is more realistic for describing large geophysical flows such as landslides, which are a threat for human facilities both in mountainous and coastal areas, as landslides entering into water are known for their tsunamigenic potential [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%